(untitled) (Bangladesh Journal of Medical Education, 2018)
This descriptive cross sectional study was carried out to assess the competencies learned by the students through ambulatory care teaching according to teachers’ and interns’ view in the undergraduate medical education in Gynaecology and Obstetrics in the medical colleges of Bangladesh. Study was conducted on nine medical colleges including five Public medical colleges and four Private medical colleges. Total 58 teachers & 567 interns participated in the study, and Separate self-administered semi structured questionnaire were used to collect their valuable opinions. Most of the teachers mentioned that through ambulatory care teaching students are taught: to greet a patient on arrival; to take history; to take consent before examining a patient; to maintain privacy during examining a patient; to do general examination of a patient; to examine a pregnant patient Most of the interns mentioned that through ambulatory care teaching the competencies learned by the students are: taking history, maintaining confidentiality, maintain privacy during examination, examining a pelvic mass, interpreting investigation reports, making provisional diagnosis. Students also observed the procedure of VIA test, and steps of PAP’s test. The study recommends that all clinical teachers should have clear knowledge about ambulatory care teaching & every institute should foster feasible teaching and learning environment. Bangladesh Journal of Medical Education Vol.9(1) 2018: 18-20